Education, Work, and Motherhood in Low and Middle Income Countries: A Review of Equality Challenges and Opportunities for Women with Disabilities - Tefera, Belaynesh (Social Inclusion, 2018)
This study looks at the equality challenges and opportunities for women with disabilities in low and middle income countries (LMICs) to participate and succeed in education, employment and motherhood. It is based on a systematic review of the literature from academic and non-governmental organization databases. The search of these databases yielded 24 articles, which were subsequently passed through open, axial, and selective coding. The resulting review found that women with disabilities in LMICs have severe difficulty participating and succeeding in education, employment and motherhood due to a number of interrelated factors: (i) hampered access to education, employment, intimacy and marriage, (ii) stigma and cultural practices resulting in discrimination and prejudice, and (iii) lack of support from family, teachers and institutions—all of which are exacerbated by poverty. Support from families, communities, the government, and non-governmental organizations improves women’s ability to fulfil their social roles (as students, employees and mothers), resulting in a better quality of life. Strategies that create awareness, minimize poverty and facilitate justice may improve the opportunities for women with disabilities in LMICs to participate in education, employment and motherhood, as well as their ability to succeed in these domains.